Elucidating the endophytic bacterial and fungal community composition and diversity in the tree fern Alsophila spinulosa through meta-amplicon sequencing - Chen, Xiaohong; Dou, Mengke; Li, Yuanhui; Su, Jialan; Zhao, Anjiu; Huang, Xiong (Frontiers in Microbiology, 2024)
Plant tissues harbor abundant endophytes, which are crucial for plant growth. Endophytes present in Alsophila spinulosa, which is enriched with medicinal components, have not been isolated and characterized yet. Here we employed metaamplicon sequencing to identify endophytic species and examined their diversity in the leaves, petioles, roots and stems of A. spinulosa. Our findings revealed 1,247 operational taxonomic units (OTUs) for endophytic bacteria across 210 species and 476 OTUs for endophytic fungi across 222 species. Alpha diversity analysis showed the highest endophytic bacterial diversity in A. spinulosa roots, whereas fungal diversity was similar across the leaf, petiole and root tissues. Fungal diversity in the leaves and petioles was markedly higher than that in the stems. Furthermore, beta diversity analysis revealed similarities in the endophytic bacterial and fungal compositions between the leaves and petioles, whereas the compositions in roots and stems considerably differed from those in the leaves and petioles. At the genus level, the predominant endophytic bacteria were Methylobacterium-Methylorubrum and Pseudomonas, whereas the predominant endophytic fungi were Cutaneotrichosporon and Pseudofabraea. Linear discriminant analysis effect size revealed characteristic endophytic bacterial genera specific to each tissue type and characteristic endophytic fungal genera specifically in the leaves, petioles and roots. The co-occurrence network analysis indicated that the complexity of endophyte networks was the highest in the leaves and the lowest in the stems of A. spinulosa. Overall, this study elucidates the distribution patterns of endophytes in A. spinulosa across various tissues, offering valuable microbial resources for the development of natural products for medicinal application.